Indonesia’s Financial System Stability: Effects of Domestic and Global Factors - Syifa Rifa Rosyadah; Hermanto Siregar; Fahmi Salam Ahmad (AI, Big Data and Quantitative Methods in Finance, 2026)
Background: DFinancial system stability is essential for ensuring efficient financial intermediation and sustainable economic growth. With increasing global financial integration, the stability of a country’s financial system is no longer determined solely by domestic conditions, but is also influenced by global factors through various transmission channels such as capital flows, exchange rates, and financial markets.Purpose: This study aims to examine the effects of both domestic and global factors on Indonesia’s financial system stability and to distinguish their impacts in the short run and the long run.Design/methodology/approach: This study employs monthly time series data from July 2003 to November 2022. Financial system stability is proxied by the Financial Stress Index (FSI). The analysis uses the Auto Regressive Distributed Lag (ARDL) model and Error Correction Model (ECM) to capture both short-run dynamics and long-run relationships.Findings/Result: The results show that, in the short run, Indonesia’s financial system stability is significantly influenced by domestic lending rates, exchange rates, money supply, U.S. financial stress, and crisis conditions. In the long run, exchange rates, money supply, and foreign exchange reserves are found to have significant effects on financial system stability. The model also indicates a speed of adjustment toward long-run equilibrium of approximately 19.9 percent per period.Conclusion: Indonesia’s financial system stability is jointly determined by domestic and global factors, with distinct roles across time horizons. These findings highlight the importance of policy responses that are not only domestically oriented but also responsive to global economic and financial developments.Originality/value (State of the art): This study contributes to the literature by integrating domestic and global determinants of financial system stability within a unified ARDL-ECM framework. Unlike prior studies that typically focus on either domestic or external factors, this research provides a more comprehensive perspective by demonstrating the combined and time-varying influence of both, particularly in the context of a small open economy like Indonesia. Keywords:ARDL-ECM, domestic factors, financial stress index, financial system stability,  global factors